The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1128/jb.00393-13
|View full text |Cite
|
Sign up to set email alerts
|

Role of Autofluorescence in Flow Cytometric Analysis of Escherichia coli Treated with Bactericidal Antibiotics

Abstract: bBactericidal antibiotics kill by different mechanisms as a result of a specific interaction with their cellular targets. Over the past few years, alternative explanations for cidality have been proposed based on a postulated common pathway, depending on the intracellular production of reactive oxygen species. Detection of hydroxyl radicals relies on staining with specific fluorescent dyes that can penetrate the cell and are detected using flow cytometry. Flow cytometry has become an important tool in microbio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
65
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 47 publications
(85 reference statements)
5
65
0
Order By: Relevance
“…Fourth, we used two dyes based on different chemistries that have been widely used for ROS detection in previous studies (3, 12, 25): 3′-(p-hydroxyphenyl) fluorescein (HPF) and 5/6-chloromethyl-2′,7′-dichlorodihydrofluorescein diacetate (CM-H2DCFDA), whose fluorescence has been shown to correlate with O 2 − production determined by direct measurement (24). For both dyes, we observed statistically significant increases in fluorescence compared with controls for maltose-induced autofluorescence and morphology changes (26,27) in the absence of a dye (Fig. 2D).…”
Section: Male-lacz Induction Is Not Lethal In Anaerobic Conditions Bumentioning
confidence: 56%
“…Fourth, we used two dyes based on different chemistries that have been widely used for ROS detection in previous studies (3, 12, 25): 3′-(p-hydroxyphenyl) fluorescein (HPF) and 5/6-chloromethyl-2′,7′-dichlorodihydrofluorescein diacetate (CM-H2DCFDA), whose fluorescence has been shown to correlate with O 2 − production determined by direct measurement (24). For both dyes, we observed statistically significant increases in fluorescence compared with controls for maltose-induced autofluorescence and morphology changes (26,27) in the absence of a dye (Fig. 2D).…”
Section: Male-lacz Induction Is Not Lethal In Anaerobic Conditions Bumentioning
confidence: 56%
“…It is unlikely that activation of all dyes would result from nonspecific or confounding chemical events and oxidizing species. We found that for the majority of dyes tested, wild-type cells treated with ampicillin (a β-lactam), gentamicin (an aminoglycoside), or norfloxacin (a fluoroquinolone) exhibited statistically significant increases in fluorescence compared with controls for antibiotic treatment-related autofluorescence (55), in which no dye was added. Collectively, the broad activation of these dyes suggests several different reactive species that may damage biomolecules are produced in response to antibiotic treatment.…”
Section: Resultsmentioning
confidence: 95%
“…Thus, we disregarded the results of HPF assays. Similar criticism about the use of HPF was raised recently concerning the interference between the autofluorescence of cells with the actual fluorescence in the presence of the probe, especially upon antibiotic treatment (32).…”
Section: Resultsmentioning
confidence: 99%